The answer is: "3" .
_______________________________
Use the Pythagorean theorem (for right triangles):
a² + b² = c² ;
in which "a = "side length 1" (unknown; for which we which to solve);
"b" = "side length 2" = "√3" (given in the figure) ;
"c" = "length of hypotenuse" = "2√3" (given in the figure);
_____________________________________________________
a² + b² = c² ;
a² = c² − b² ;
Plug in the known values for "c" and "b" ;
a² = (2√3)² − (√3)² ;
Simplify:
(2√3)² = 2² * (√3)² = 2 * 2 * (√3√3) = 4 * 3 = 12 .
(√3)² = (√3√3) = 3 .
a² = 12 − 3 = 9 .
a² = 9
Take the "positive square root" of EACH SIDE of the equation; to isolate "a" on one side of the equation; & to solve for "a" ;
+√(a²) = +√9 ;
a = 3 .
____________________________________
The answer is: "3" .
____________________________________
The parts of algebraic expressions related to polynomials are variables and coefficients.
<h3>What are the parts of algebraic expressions?</h3>
The parts of algebraic expressions are;
- Variables which are letters that represent numbers
- Coefficients are numbers that multiply the variables
- Constant is a number that is not multiplied by any variable
Polynomials are algebraic expressions composed of variables, constants and exponents, that are combined using the mathematical operations such as addition, subtraction, and multiplication
Polynomials consists of variables and coefficients. The variables in polynomials are also called indeterminates. The coefficients also multiply this variables.
Thus, the parts of algebraic expressions related to polynomials are variables and coefficients.
Learn more about algebraic expressions here:
brainly.com/question/4344214
#SPJ1
Let
. Then
. Note that
.
Recall that for
, we have
![\displaystyle\frac1{1-x}=\sum_{n\ge0}x^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cfrac1%7B1-x%7D%3D%5Csum_%7Bn%5Cge0%7Dx%5En)
This means that for
, or
, we have
![\displaystyle f'(x)=\frac1{1+x^2}=\frac1{1-(-x^2)}=\sum_{n\ge0}(-x^2)^n=\sum_{n\ge0}(-1)^nx^{2n}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%3D%5Cfrac1%7B1%2Bx%5E2%7D%3D%5Cfrac1%7B1-%28-x%5E2%29%7D%3D%5Csum_%7Bn%5Cge0%7D%28-x%5E2%29%5En%3D%5Csum_%7Bn%5Cge0%7D%28-1%29%5Enx%5E%7B2n%7D)
Integrate the series to get
![f(x)=f(0)+\displaystyle\sum_{n\ge0}\frac{(-1)^n}{2n+1}x^{2n+1}](https://tex.z-dn.net/?f=f%28x%29%3Df%280%29%2B%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%5Cfrac%7B%28-1%29%5En%7D%7B2n%2B1%7Dx%5E%7B2n%2B1%7D)
![\implies\tan^{-1}x=\displaystyle\sum_{n\ge0}\frac{(-1)^n}{2n+1}x^{2n+1}](https://tex.z-dn.net/?f=%5Cimplies%5Ctan%5E%7B-1%7Dx%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%5Cfrac%7B%28-1%29%5En%7D%7B2n%2B1%7Dx%5E%7B2n%2B1%7D)
Answer:
93.6 inch^2
Step-by-step explanation:
sides=6 side-length=6 inches Apothem= 5.2 inches Area= 6*(1/2)(6)(5.2)